PENGARUH UTANG LUAR NEGERI DAN DANA PERIMBANGAN TERHADAP PERTUMBUHAN EKONOMI INDONESIA - B01109042, EKO SUPRIYANTO (Jurnal Pembangunan dan Pemerataan, 2014)
Foreign debt and balancing fund aims to increase economic growth in Indonesia. Foreign debt is used to fund the construction and fill the country's needs while balancing funds are used to fund the construction areas that have an impact on national growth. The title of this research is the influence of foreign debt and the balancing funds to the economic growth of Indonesia. This study used a descriptive quantitative method, to see the effect of independent variables (the foreign debt and balancing fund) on the dependent variable (economic growth) in Indonesia by using multiple linear regression models, and statistical analysis tools that the t test and the coefficient of determination to test the hypothesis whether foreign debt and balancing fund effect on the economic growth. The results of this study indicate that the positive effect of foreign debt amounted to 0,009 to economic growth and the balance of funds is also a positive effect of 0.0006 and both variables are equally significant. Variations of the foreign debt and balancing fund can only explain 49% and the rest are influenced by other factors. Foreign debt has a significant impact in promoting economic growth while balancing funds do not have a large impact in influencing economic growth. Keywords: Foreign Debt, Balancing Funds, and Economic Growth Â